Socio-economic, environmental and health impacts of dietary transformation in Bangladesh - de Lange, Thijs; van Dijk, Michiel; Kuiper, Marijke; van Zeist, Willem-Jan; Bartelings, Heleen; Mizan, Arefin (IOP Publishing, 2025)
The transition to healthier diets might be accompanied by trade-offs that occur in other parts of the food system. In this study the trade-offs between socio-economic, environmental, and health indicators were analyzed in different dietary scenarios for Bangladesh between 2022 and 2050. We used a global economic simulation model with updated national food consumption data, extended with a footprint module to track environmental impacts through the food value chain in Bangladesh and its trading partners. This study compares a business-as-usual (BAU) diet with the EAT-Lancet diet and the Bangladesh food-based dietary guidelines (FBDGs). The BAU diet has a higher intake of animal products and sugar, and a lower intake of vegetables, fruits, legumes, and nuts than the EAT-Lancet and FBDG diets. We found that promoting a diet with more plant-based proteins has a strong positive impact on dietary health and an overall positive impact on the environment compared to the BAU scenario. This is due to the reduced impact of animal protein production on greenhouse gas emissions and the reduced impact of rice production on water use and nitrogen application. In addition, the transition to sustainable and healthy diets had minor impacts on the wages of low-skilled workers, Bangladesh's self-sufficiency, and the affordability of food and cereals. In particular, the FDBG diet scenario scored best on diet and cereal affordability, as well as freshwater use compared to the other two scenarios. The decrease in the self-sufficiency ratio was comparable to the BAU diet scenario and smaller compared to the EAT-Lancet diet.